Hydatid renal cyst - Guitton Arteaga, Walter (2021)
Hydatidosis is a parasitosis produced by Echinococcus larvae, which form cysts frequently located in the liver and lung; Renal location has only been reported in 4% of visceral forms. We present the case of a 19-year-old man from Lima, who came to our hospital with pain in the left flank and hematuria, a tomography was performed suggestive of complicated simple cyst. A nephrectomy is performed and the piece is sent to the Pathology Department, in which they observe cystic formation inside which multiple folded whitish membranes are observed: in the microscopic examination anhistic membranes are observed, consistent with a renal hydatid cyst.